400 Safety and Efficacy of the Off-label Use of Pipeline Embolization Device Based on the 2018 FDA Approved Indications for Intracranial Aneurysms: A Single Center Retrospective Cohort Study. (1st April 2022) - Enriquez-Marulanda, Alejandro; Penumaka, Anirudh; Ogilvy, Christopher S.; Thomas, Ajith J.; Moore, Justin M.
Abstract : INTRODUCTION: The Pipeline embolization device (PED) has proven to be safe and effective for treating selected intracranial aneurysms. The versatility and the popularity of this device have driven increased interest in expanding the latest 2018 FDA-approved indications. METHODS: Retrospective analysis of aneurysms treated with PED at a single center from 2013-2019 was performed. Comparisons were made based on the compliance to the 2018 FDA-approved indications. Univariate comparisons and longitudinal analysis were performed. RESULTS: A total of 492 treated aneurysms were included, from which 65.2% were considered on-label and 34.8% off-label. Aneurysm complete and near-complete occlusion rate was non-significantly lower in the off-label group (80.9% vs 85.7%; p=0.19). Off-label treatment had higher rate of poor functional outcomes defined as modified Rankin scale > 2 (10.3% vs 3.5%; p=0.002). Although baseline pre-treatment mRS was already higher in the off-label group (10.3% vs 3.5%; p<0.001). There were no differences in retreatment, thromboembolic complications, intracranial hemorrhagic complications, and mortality rates. CONCLUSION: Off-label treatment with PED may be considered for select aneurysms, which are challenging to treat with other techniques (clipping, coiling, etc.). These cases have similar complete and near-complete occlusion rates compared to on-label cases. There are, however, potential higher risks of poor functional outcomes.